Essential Thrombocythemia Masquerading as Henoch–Schonlein Purpura in a 9-year-old Child - Palanisamy Sivamurukan; Sriram Krishnamurthy; C G Delhikumar; Anbazhagan Jagadeesh; Bheemanathi Hanuman Srinivas; Debdatta Basu (Indian Journal of Rheumatology)
Leukocytoclastic vasculitis (LCV) is a complex group of conditions which are characterized by vascular damage and neutrophilic infiltrates. LCV in children is usually considered as a part of connective tissue diseases, autoimmune disorders, and primary systemic vasculitis such as systemic lupus erythematosus (SLE) or Henoch–Schonlein purpura (HSP). We herein describe a 9-year-old child with fever, arthritis, diffuse abdominal pain, and palpable purpura over the lower limbs, who was initially diagnosed to have HSP based on the European League Against Rheumatism criteria. He also had thrombocytosis which was attributed to HSP. The skin biopsy showed LCV, providing corroborative evidence of HSP in this setting. Due to severe abdominal pain, prednisolone was prescribed, and resolution of symptoms occurred. There was no hepatosplenomegaly, anemia, polycythemia, or lymphadenopathy at this juncture. On follow-up, however, the thrombocytosis worsened (2000 × 109/L) with appearance of a palpable spleen. Further investigations revealed essential thrombocythemia (ET) as the etiology of LCV in this child. The learning point in this case report is the emphasis on consideration of inclusion of malignancies in the spectrum of LCV in children, besides the usual differential diagnosis such as HSP or SLE, especially when accompanied by worsening thrombocytosis. ET has not been reported in the constellation of malignancies described in association with LCV in the literature.